Study of the Electric Spark and Combustion Characteristic Times in a Mike 3 Apparatus - Elisabetta Sieni; Marco Barozzi; Martina Scotton; Rajeswari Sundararajan; Patrizia Lamberti; Sabrina Copelli (Chemical Engineering Transactions, 2023)
Understanding how dust can ignite and explode in an industrial contest is an important and complex task, and much of the work around this is mainly performed via experimental measurements, in accordance to specific standards. However, those same properties are straightforwardly closely related to the nature of the experimental tests. Among these, the Minimum Ignition Energy (MIE) of a dust cloud, that is usually measured in a MIKE 3 apparatus, can be affected by several factors, as: delay time of the electric spark with respect to the dust-air dispersion formation inside the apparatus, dust concentration, humidity content, dust granulometry, etc. The delay time is one of the worst parameters to adjust, because the fluid-dynamics of the dust-air mixture inside the tube is not easily predictable. Within this work, a study on the characteristic times of all the relevant phenomena occurring within a MIKE 3 apparatus was done by means of slow-motion videos of the tests. Particularly, three different characteristic times were compared referring to a given sample of niacin dust: dust lifting and settling times, effective spark delay time (that is, the time at which the spark is visible) and combustion time (that is, the time at which the flame is visible). According to the results, the effective delay time is almost always quite different with respect to the theoretical one, influencing the effective concentration of dust between the electrodes and, finally, the possibility to have a flame ignition or not within the apparatus. This means that the value of the MIE parameter can be profoundly influenced by the effective delay. Keywords: Process Safety; Dust Explosions; Minimum Ignition Energy; Spark Delay